Solution to Fuzzy Multi-Objective Assignment Problems using Diagonal Optimal Method - Beaula, Thangaraj; Saravanan, S. (Communications in Mathematics and Applications, 2022)
In this paper a new algorithm diagonal optimal method is proposed to obtain optimal solution to fuzzy multi-objective assignment problem with several fuzzy parameters. The method is illustrated with a numerical example.
Keywords: Fuzzy multi-objective assignment problem; Trapezoidal fuzzy number; Ranking of fuzzy numbers; Diagonal optimal method